Telepathology and Optical Biopsy - Olga Ferrer-Roca (International Journal of Telemedicine and Applications)
The ability to obtain information about the structure of tissue without taking a sample for pathology has opened the way for new diagnostic techniques. The present paper reviews all currently available techniques capable of producing an optical biopsy, with or without morphological images. Most of these techniques are carried out by physicians who are not specialized in pathology and therefore not trained to interpret the results as a pathologist would. In these cases, the use of telepathology or distant consultation techniques is essential.